Dosimetric comparison of preoperative single‐fraction partial breast radiotherapy techniques: 3D CRT, noncoplanar IMRT, coplanar IMRT, and VMAT. (8th January 2015) - Yoo, Sua; Blitzblau, Rachel; Yin, Fang‐Fang; Horton, Janet K.
Abstract : The purpose of this study was to compare dosimetric parameters of treatment plans among four techniques for preoperative single‐fraction partial breast radiotherapy in order to select an optimal treatment technique. The techniques evaluated were noncoplanar 3D conformal radiation therapy (3D CRT), noncoplanar intensity‐modulated radiation therapy ( IMRT NC ), coplanar IMRT ( IMRT CO ), and volumetric‐modulated arc therapy (VMAT). The planning CT scans of 16 patients in the prone position were used in this study, with the single‐fraction prescription doses of 15 Gy for the first eight patients and 18 Gy for the remaining eight patients. Six (6) MV photon beams were designed to avoid the heart and contralateral breast. Optimization for IMRT and VMAT was performed to reduce the dose to the skin and normal breast. All plans were normalized such that 100% of the prescribed dose covered greater than 95% of the clinical target volume (CTV) consisting of gross tumor volume (GTV) plus 1.5 cm margin. Mean homogeneity index (HI) was the lowest ( 1.05 ± 0.02 ) for 3D CRT and the highest ( 1.11 ± 0.04 ) for VMAT. Mean conformity index (CI) was the lowest ( 1.42 ± 0.32 ) for IMRT NC and the highest ( 1.60 ± 0.32 ) for VMAT. Mean of the maximum point dose to skin was the lowest ( 73.7 ± 11.5 % ) for IMRT NC and the highest ( 86.5 ± 6.68 % ) for 3D CRT. IMRT CO showed very similar HI, CI, and maximum skin dose to IMRT NC ( differences < 1 % ). The estimated mean treatment delivery time, excluding the time spent for patient positioning and imaging, was 7.0 ± 1.0, 8.3 ± 1.1, 9.7 ± 1.0, and 11.0 ± 1.5 min for VMAT, IMRT CO, IMRT NC and 3D CRT, respectively. In comparison of all four techniques for preoperative single‐fraction partial breast radiotherapy, we can conclude that noncoplanar or coplanar IMRT were optimal in this study as IMRT plans provided homogeneous and conformal target coverage, skin sparing, and relatively short treatment delivery time. PACS numbers: 81.40.Wx, 87.55.D‐